Construction of anti-parallel G-quadruplexes through sequential templated click1. Issue 23 (21st March 2015) - Bonnet, Romaric; Lavergne, Thomas; Gennaro, Béatrice; Spinelli, Nicolas; Defrancq, Eric
<x xml:space="preserve">Abstract</x> Biologically relevant anti-parallel DNA G-quadruplexes were constrained and stabilised onto addressable cyclopeptide scaffolds through sequential oxime and CuAAc reactions.